2022
DOI: 10.1155/2022/7774283
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Application Value of Ultrasound Three-Dimensional Speckle Tracking Technology Combined with Thyroid Autoantibodies and Hormones in the Diagnosis and Treatment of Graves’ Disease

Abstract: Objective. The aim of the study is to evaluate the application value of three-dimensional speckle tracking imaging (3D-STI) and combined detection of thyroid autoantibodies and hormones in the diagnosis and treatment of Graves’ disease. Methods. A total of 60 patients with Graves’ disease enrolled in our hospital from February 2020 to February 2021 were included in the experimental group, and 60 healthy patients after a physical examination during the same period were selected as the control group. No interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%